Determining the Degree of Genetic Relationship Among Wild Almond (Prunus amygdalus) Species Spread in the Central and Southwestern Regionbof Syria (Damascus University Journal of agriculture sciences, 2023)
The research was carried out in the Biotechnology Laboratory of the Faculty of Agriculture at Damascus University / Syria in the year 2020-2021. The study was conducted on almond species spread in five main regions to determine the degree of genetic relationship among them using the ISSR (Inter Simple Sequence Repeats) technique, 23 primers were used for this purpose, and 21 primers of them gave polymorphism among the studied species. The use of these primers resulted in a total of 95 bands, 93 of them were polymorphic, and the polymorphism ratio was 96.51%. The number of polymorphic bands ranged between 2 bands with the primers (P-8 and P-15), and 6 bands with the primers (P-30, P-36 and P-37) with an average of 4.42 bands for each primer, and the average polymorphic information content coefficient ranged between 0.0525 with the primer P-8 and 0.4998 with the primer P-25, with an average of 0.4132. The percentage of genetic distance ranged between 46 and 92%, and the lowest value was 46% between the two species, A. communis and A. korschinskii. This low value of genetic distance indicates a large degree of genetic relationship. While the highest value of genetic divergence was 92% between the two species A.spartioïdes and A. arabica, which indicates that there is a large genetic variation between them. It was noted that the tree was divided into two main clusters, the A. orientalis genotype was unique to the first cluster, while the second cluster included the other genotypes divided into two sub-clusters with varying degrees of genetic relationship. Our results indicate the possibility of using the ISSR technique to study genetic relationship among wild almond cultivars.
Keywords: genetic relationship; wild almond; Syria; ISSR technique